2003
DOI: 10.1074/jbc.m210876200
|View full text |Cite
|
Sign up to set email alerts
|

Bombesin, Lysophosphatidic Acid, and Epidermal Growth Factor Rapidly Stimulate Focal Adhesion Kinase Phosphorylation at Ser-910

Abstract: A rapid increase in the tyrosine phosphorylation of the nonreceptor tyrosine kinase FAK 1 (1, 2), which localizes to focal adhesion plaques (3), has been identified as a prominent early event in cells stimulated by diverse signaling molecules that regulate cell proliferation, migration, and apoptosis (4, 5 (14,27). Phosphorylation at Tyr-925 within the focal adhesion targeting (FAT) domain creates a binding site for the Src homology 2 domain of the adapter protein Grb2-SOS (Ras exchange factor) complex and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
103
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 97 publications
(113 citation statements)
references
References 89 publications
7
103
3
Order By: Relevance
“…Interestingly, both Ser-910 and Ser-843, located in the COOH-terminal region of FAK, have been identified as prominent phosphorylation sites during mitosis [33]. Recent results from our laboratory demonstrated that FAK phosphorylation at Ser-910 was strikingly stimulated by GPCR agonists, tumor promoting phorbol esters and growth factors in Swiss 3T3 fibroblasts [34][35][36]. Furthermore, phosphorylation of FAK at Ser-843 was induced by GPCR agonists, including bombesin, vasopressin and bradykinin in Swiss 3T3 fibroblasts [37].…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…Interestingly, both Ser-910 and Ser-843, located in the COOH-terminal region of FAK, have been identified as prominent phosphorylation sites during mitosis [33]. Recent results from our laboratory demonstrated that FAK phosphorylation at Ser-910 was strikingly stimulated by GPCR agonists, tumor promoting phorbol esters and growth factors in Swiss 3T3 fibroblasts [34][35][36]. Furthermore, phosphorylation of FAK at Ser-843 was induced by GPCR agonists, including bombesin, vasopressin and bradykinin in Swiss 3T3 fibroblasts [37].…”
Section: Discussionmentioning
confidence: 92%
“…In fibroblasts, we proposed that FAK serves as a point of integration of signals transmitted via Gα q , leading to PKC/ERK-dependent FAK phosphorylation at Ser-910 [34][35][36] and to Ca 2+ /calmodulin/CaMKII-dependent FAK phosphorylation at Ser-843 [37]. Here, we examined whether these pathways also operate in intestinal epithelial cells.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations